Cilostazol for secondary stroke prevention: systematic review and meta-analysis - Tan, Choon Han; Wu, Andrew GR; Sia, Ching-Hui; Leow, Aloysius ST; Chan, Bernard PL; Sharma, Vijay Kumar; Yeo, Leonard LL; Tan, Benjamin YQ (Stroke and vascular neurology, 2021)
BackgroundStroke is one of the leading causes of death worldwide. Cilostazol, an antiplatelet and phosphodiesterase 3 inhibitor, has not been clearly established for ischaemic stroke use. We aim to determine the efficacy and safety of cilostazol for secondary stroke prevention.MethodsMEDLINE, EMBASE, Cochrane Library, Web of Science and ClinicalTrials.gov were searched from inception to 25 September 2020, for randomised trials comparing the efficacy and safety of cilostazol monotherapy or dual therapy with another antiplatelet regimen or placebo, in patients with ischaemic stroke. Version 2 of the Cochrane risk-of-bias tool for randomised trials (RoB 2) was used to assess study quality. This meta-analysis was reported in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement.ResultsEighteen randomised trials comprising 11 429 participants were included in this meta-analysis. Most trials possessed low risk of bias and were of low heterogeneity. Cilostazol significantly reduced the rate of ischaemic stroke recurrence (risk ratio, RR=0.69, 95% CI 0.58 to 0.81), any stroke recurrence (RR=0.64, 95% CI 0.54 to 0.74) and major adverse cardiovascular events (RR=0.67, 95% CI 0.56 to 0.81). Cilostazol did not significantly decrease mortality (RR=0.90, 95% CI 0.64 to 1.25) or increase the rate of good functional outcome (Modified Rankin Scale score of 0–1; RR=1.07, 95% CI 0.95 to 1.19). Cilostazol demonstrated favourable safety profile, significantly reducing the risk of intracranial haemorrhage (RR=0.46, 95% CI 0.31 to 0.68) and major haemorrhagic events (RR=0.49, 95% CI 0.34 to 0.70).ConclusionsCilostazol demonstrated superior efficacy and safety profiles compared with traditional antiplatelet regimens such as aspirin and clopidogrel for secondary stroke prevention but does not appear to affect functional outcomes. Future randomised trials can be conducted outside East Asia, or compare cilostazol with a wider range of antiplatelet agents.